Residents’ perceptions of simulation as a clinical learning approach - Walsh, Catharine M; Garg, Ankit; Ng, Stella L; Goyal, Fenny; Grover, Samir C. (Canadian Medical Education Journal, 2017)
Background: Simulation is increasingly being integrated into medical education; however, there is little research into trainees’ perceptions of this learning modality. We elicited trainees’ perceptions of simulation-based learning, to inform how simulation is developed and applied to support training. Methods: We conducted an instrumental qualitative case study entailing 36 semi-structured one-hour interviews with 12 residents enrolled in an introductory simulation-based course. Trainees were interviewed at three time points: pre-course, post-course, and 4-6 weeks later. Interview transcripts were analyzed using a qualitative descriptive analytic approach. Results: Residents’ perceptions of simulation included: 1) simulation serves pragmatic purposes; 2) simulation provides a safe space; 3) simulation presents perils and pitfalls; and 4) optimal design for simulation: integration and tension. Key findings included residents’ markedly narrow perception of simulation’s capacity to support non-technical skills development or its use beyond introductory learning. Conclusion: Trainees’ learning expectations of simulation were restricted. Educators should critically attend to the way they present simulation to learners as, based on theories of problem-framing, trainees’ a priori perceptions may delimit the focus of their learning experiences. If they view simulation as merely a replica of real cases for the purpose of practicing basic skills, they may fail to benefit from the full scope of learning opportunities afforded by simulation.